A step-by-step translation of evidence into a psychosocial intervention for everyday activities in dementia: a focus group study. (4th March 2018) - Giebel, Clarissa M.; Challis, David; Hooper, Nigel M.; Ferris, Sally
ABSTRACT: Objective: In order to increase the efficacy of psychosocial interventions in dementia, a step-by-step process translating evidence and public engagement should be adhered to. This paper describes such a process by involving a two-stage focus group with people with dementia (PwD), informal carers, and staff. Methods: Based on previous evidence, general aspects of effective interventions were drawn out. These were tested in the first stage of focus groups, one with informal carers and PwD and one with staff. Findings from this stage helped shape the intervention further specifying its content. In the second stage, participants were consulted about the detailed components. Findings: The extant evidence base and focus groups helped to identify six practical and situation-specific elements worthy of consideration in planning such an intervention, including underlying theory and personal motivations for participation. Carers, PwD, and staff highlighted the importance of rapport between practitioners and PwD prior to commencing the intervention. It was also considered important that the intervention would be personalised to each individual. Conclusions: This paper shows how valuable public involvement can be to intervention development, and outlines a process of public involvement for future intervention development. The next step would be to formally test the intervention.